Organizational climate, job characteristics and commitment: A study of expatriates in institutions of higher learning in Malaysia - Barcelona, Aurora C.; Mohd. Nasurdin, Aizzat (Universiti Utara Malaysia, 1997)
Realizing the significant contributions that could be made by the academic expatriates in terms of educational innovations, transfer of knowledge, the sharing of vast array of relevant experiences, this study was undertaken. The writers hope that the findings can help local institutions of higher learning maximize the benefits involved in the cost of hiring expatriates. Using correlation analysis, significant relationships were found between organizational commitment dimensions and respondents' variables (marital status, institution, years in service, qualification); job characteristics (social and career opportunities); and organizational climate variables (structure, responsibility, reward, risk, warmth, support, standards, conflict and identity). The stepwise regression analysis on the other hand, determine that probable predictors of organizational commitment levels, such as institution, academic qualification and position title, career opportunities, structure, identity and risk. Prior knowledge of potential indicators of organizational commitment levels will help selected institutions upgrade its expatriates commitment levels. The long run effect of which is improved quality education for all, accelerated production and better services to its multiple clientele. This implies that to enhance organizational commitment levels (denoted by acceptance of organizational values, loyalty and devotion), considerable attention should be given to the alleged critical variables and predictors of organizational commitment levels.